MGMT promoter methylation in Peruvian patients with glioblastoma - Belmar-Lopez, C (2018)
Purpose: O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation predicts the outcome and response to alkylating chemotherapy in glioblastoma. The aim of this study is to evaluate the prevalence of MGMT methylation in Peruvian glioblastoma cases. Patients and methods: We evaluated retrospectively 50 cases of resected glioblastoma during the period 2008-2013 at Instituto Nacional de Enfermedades Neoplasicas in Peru. Samples consisted of paraffin embedded and frozen tumour tissue. MGMT-promoter methylation status and the expression level of MGMT gene were evaluated by methylation-specific PCR and real-time PCR, respectively. Results: Unmethylated, methylated and partially methylated statuses were found in 54%, 20% and 26% of paraffin-embedded samples, respectively. Methylation status was confirmed in the Virgen de la Salud Hospital and frozen samples. There was an association between the status of MGMT-promoter methylation and the level of gene expression (p = 0.001). Methylation was associated with increased progression-free survival (p = 0.002) and overall survival (OS) (p < 0.001). Conclusion: MGMT-promoter methylation frequency in Peruvian glioblastoma is similar to that reported in other populations and the detection test has been standardised.